HLA and rheumatoid arthritis: a combined analysis of 440 British patients. Issue 8 (August 1986) - Jaraquemada, D; Ollier, W; Awad, J; Young, A; Silman, A; Roitt, I M; Corbett, M; Hay, F; Cosh, J A; Maini, R N
Abstract : Four hundred and forty unrelated British Caucasoid patients with rheumatoid arthritis (RA) have been HLA typed for class I and class II antigens. Analyses of HLA antigen associations were performed on the overall group and in patient subsets selected according to particular disease parameters or sex, or both. The results confirm previously reported positive associations of HLA-DR4, Dw4, and DRw53 and negative associations of HLA-DR2 and DR7 with RA. Patients subsets with severe erosions, seropositivity, and features of extra-articular disease showed a stronger association, also confirming earlier reports. The link between HLA and disease severity was emphasised by a significant trend of increased Dw4 frequency with increasing severity of radiological erosions. In addition, a positive association of RA with HLA-A2 was observed and a strong negative association with DR3. The frequency of HLA-B27 was significantly increased in patients with subluxation of the spine. Differences were observed between male and female patients in relation to the HLA association. In men an increase in the frequency of the haplotype HLA/Dw4/DR4/Bw62/Cw3/A2 was observed. This showed no relationship with parameters of disease severity other than extra-articular disease. In women only class II antigens (DRw53/Dw4/DR4) showed an increased frequency. This increase was strongly associated with disease severity. A significant decrease of this class II association was observed with increasing age of disease onset; this was not seen in men.